THE SPY PAPERS. - DAVIES, NICK (Prospect, 2024)
This article provides an overview of the phone-hacking scandal in the UK and the subsequent fallout. It discusses the disclosure of new evidence, including emails and call data, suggesting that the Murdoch company may have engaged in criminal activities to spy on politicians and interfere with government decisions. The article also highlights the efforts made by News of the World executives to suppress and conceal evidence, including the deletion of emails and the use of aliases. The text emphasizes the need for responsible journalism and sheds light on the power and influence of media conglomerates.